Authentic Material Towards Students’ Ability in Comprehending Procedure Text For The Efl Leaners - Selamet Riadi Jaelani; Ari Prasetyaningrum; Astrid Dwimaulani (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The research objects were: (1) to know the effect of authentic material towards students’ ability in comprehending procedure text for the EFL Learners and (2) to know the extent effect of authentic material towards students’ ability in comprehending procedure text for the EFL Learners. This research was experimental research, with two groups of sample; those are experimental and control groups. Each group consists of 20 students, 20 students for experimental group and 20 students for control group. To get the data, the research instruments which were developed to collect data were objective test, which consisted 30 items in form of multiple-choice test where each item consists of four items option (a, b, c, and d). After collecting and calculating the data, the researcher found out that the mean scores of experimental group in pre and post-tests were 18.85 and 21.70, while for control group were 17.70 and 19.50. In testing the hypothesis, the researcher used t-test formula. The researcher found out that t-test was 3.63 and t-table in significant rank 0.05 (5%) was 2.00 (3.63 > 2.00) so, the alternative hypothesis was accepted. It means that there is a significant effect of authentic material towards students’ ability in comprehending procedure text for the EFL Learners.